2018
DOI: 10.1038/s41598-018-31241-8
|View full text |Cite
|
Sign up to set email alerts
|

YesU from Bacillus subtilis preferentially binds fucosylated glycans

Abstract: The interaction of carbohydrate-binding proteins (CBPs) with their corresponding glycan ligands is challenging to study both experimentally and computationally. This is in part due to their low binding affinity, high flexibility, and the lack of a linear sequence in carbohydrates, as exists in nucleic acids and proteins. We recently described a function-prediction technique called SPOT-Struc that identifies CBPs by global structural alignment and binding-affinity prediction. Here we experimentally determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…For ADL, LectinOracle correctly inferred the activity of its chitin-binding domain [36] and predicted motifs such as chitotriose as the top binders (Figure S1E, Supporting Information). YesU has been characterized to prefer fucosylated glycans [37] and LectinOracle also predicted fucosylated glycan motifs to be strongly enriched for binding (Figure S1F, Supporting Information), including fucosylated motifs such as Lewis X. These case studies involving lectins outside our data set emphasize that LectinOracle can be used generally to further probe the glycan-binding specificity of lectins, both already characterized as well as uncharacterized.…”
Section: Developing a Deep Learning-based Model To Predict Lectin-glycan Interactionsmentioning
confidence: 55%
“…For ADL, LectinOracle correctly inferred the activity of its chitin-binding domain [36] and predicted motifs such as chitotriose as the top binders (Figure S1E, Supporting Information). YesU has been characterized to prefer fucosylated glycans [37] and LectinOracle also predicted fucosylated glycan motifs to be strongly enriched for binding (Figure S1F, Supporting Information), including fucosylated motifs such as Lewis X. These case studies involving lectins outside our data set emphasize that LectinOracle can be used generally to further probe the glycan-binding specificity of lectins, both already characterized as well as uncharacterized.…”
Section: Developing a Deep Learning-based Model To Predict Lectin-glycan Interactionsmentioning
confidence: 55%
“…For ADL, LectinOracle correctly inferred the activity of its chitin-binding domain [32] and predicted motifs such as chitotriose as the top binders (Figure S1E). YesU has been characterized to prefer fucosylated glycans [33] and LectinOracle also predicted fucosylated glycan motifs to be strongly enriched for binding (Figure S1F), including fucosylated motifs such as Lewis X. These case studies involving lectins outside our dataset emphasize that LectinOracle can be used generally to further probe the glycan-binding specificity of lectins, both already characterized as well as uncharacterized.…”
Section: Protein Armmentioning
confidence: 59%
“…This work demonstrated that the APTES-GOPTS ratio can be used to control the surface potential and subsequent cell adhesion. 56 The current GOPTS-generated glycan array was compared to our in-house glycan arrays printed on SE3 slides 39,49 revealing comparable glycosylamine deposition. A statistical comparison of binding and nonbinding events revealed 78.5% homology between the arrays (Supporting Information Figures S1 and S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Glycan arrays consisting of 172 diverse glycans (DextraLabs) in the absence of spacers were taken from existing glycan libraries. ,, Glycans were amine functionalized as previously published by Day et al Glycan arrays were fabricated as previously published by Tiralongo et al In brief, glycosylamines were suspended in 1:1 DMF/dimethyl sulfoxide (DMSO) at a concentration of 500 μM and printed onto 3C-SiC GOPTS slides, 3C-SiC APTES slides, and SuperEpoxy3 glass slides (SE3) (ArrayIt) using a SpotBot Extreme array spotter (ArrayIT) in a six-pin subarray print per glass slide format. All glycans were printed in replicates of four, including four AlexaFlour 555/647 and FITC control spots, per subarray using 946MP4 pins and a contact time of 1 s at 50% relative humidity, with pins being reloaded after every 12 spots.…”
Section: Methodsmentioning
confidence: 99%